PARAMETRICAL OPTIMIZATION OF AN OPTIC – ELECTRONIC DEVICE IN PROCESS OF DISCOVERING DISTANT OBJECTS: PARAMETRICAL OPTIMIZATION OF AN OPTIC – ELECTRONIC DEVICE IN PROCESS OF DISCOVERING DISTANT OBJECTS - Zhekov, Zhivko; Stoyanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The process of discovering distant objects through the use of optic – electronic device has been examined, with an optical device - visir - for preliminary "rough" targeting. Methods for optimization and determining the optimal values of the crucial parameters of the device in regime for discovering of distant objects has been proposed, thus ensuring its maximum sensitivity.